Seventeen Australian Artists. - Galleria San Vidal, Venezia; Biennale di Venezia, 1988 - pav. Australië (Brisbane : Ray Hughes Gallery, 1988)
Allen, Davida ; Cole, Peter ; Furlonger, Joe ; Killick, Stephen ; Looby, Keith ; Nedelkopoulos, Nicholas ; Morris, Robert J. ; Pople, Rodney ; Powditch, Peter ; Risley, Tom ; Robinson, William ; Smith, Ian ; Tupicoff, June ; Twigg, Tony ; Whisson, Ken ; Withers, Rod ; Yaxley, William
Seventeen Australian Artists / Diciassette Artisti Australiani, Galleria San Vidal, Venezia, 18 Giunio - 2 Luglio 1988. Biennale di Venezia, 1988
Italiaans & Engels
kunstcatalogus
Keywords: Australië